2016
DOI: 10.1021/acs.energyfuels.6b01170
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Nanoaggregation in Asphaltene Mixtures: Effects of the N, O, and S Heteroatoms

Abstract: In this paper the aggregation of asphaltenes is studied for two asphaltene molecule families, namely PA3 and CA22 analogues, based on the work of Schuler et al. (JACS, 2015, 137, 31, 9870). The chemical characteristics of these molecules were screened by changing the heteroatoms on the backbone and the lateral chain-ends. These molecules were mixed together with different relative concentrations and for the first time the aggregation of different asphaltenes was determined using molecular dynamics simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 49 publications
4
80
0
Order By: Relevance
“…Results indicate that van der Waals forces are the prevailing interaction between asphaltenes. This finding is in line with many previous MD studies that reported asphaltene aggregation (see for example: Khalaf and Mansoori, 2018;Sedghi et al, 2013;Silva et al, 2016). PW group exhibits the greatest attraction between asphaltene molecules.…”
Section: Potential Energies Of Asphaltenessupporting
confidence: 92%
“…Results indicate that van der Waals forces are the prevailing interaction between asphaltenes. This finding is in line with many previous MD studies that reported asphaltene aggregation (see for example: Khalaf and Mansoori, 2018;Sedghi et al, 2013;Silva et al, 2016). PW group exhibits the greatest attraction between asphaltene molecules.…”
Section: Potential Energies Of Asphaltenessupporting
confidence: 92%
“…In previous work based on molecular dynamics simulations, we have shown that (i) polar acidic lateral chains play a major role favoring this aggregation pattern 18,19 and (ii) porphyrins are inherently present in these molecular aggregates forming multiple H-bonds with asphaltenes and water. 20 More particularly, we have also shown that vanadium porphyrins play an important role on asphaltene aggregation and water/oil interfacial activity.…”
Section: Introductionmentioning
confidence: 87%
“…It does not depend on the polarity of the conjugated core (the presence of heteroatoms) (Sedghi and Goual 2009;Sedghi et al 2013), even if the stability (energy of interaction) of the nanoaggregate indeed does (Santos Silva et al 2016). However, given the range of energies found for the π − π interactions, asphaltene decomposition (coke formation) would take place before any dissociation of this interaction could be achieved (Takanohashi et al 2003).…”
Section: Proposition Of a Structure-function Linkmentioning
confidence: 99%